2019
DOI: 10.3390/molecules24071395
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Enhances Heat Tolerance of Rice Seeds by Modulating Endogenous Starch and Polyamine Metabolism

Abstract: Polyamines have been reported to be involved in grain filling and they might contribute to the construction of heat resistance of some cereals. In this study, the hybrid rice ‘YLY 689’ was used to explore the possible effects of exogenous spermidine (Spd) on seed quality under high temperature during the filling stage. Rice spikes were treated with Spd or its synthesis inhibitor cyclohexylamine (CHA) after pollination, and then the rice plants were transferred to 40 °C for 5-day heat treatment. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
9
33
0
Order By: Relevance
“…In the present study, GABA induced starch catabolism, which is of primary importance for providing available carbohydrates for seed germination and growth under osmotic stress, salinity and the combined stress. These findings are consistent with previous studies, which found that environmental stresses such as osmotic stress, salt and heat stress decreased seed germination due to the inhibition of starch catabolism under these conditions [29,36,37]. It has been found that the metabolite mobilization of starch and soluble sugars is critical for the maintenance of cell turgor and energy sources when seeds are subjected to salinity and osmotic stress [36].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, GABA induced starch catabolism, which is of primary importance for providing available carbohydrates for seed germination and growth under osmotic stress, salinity and the combined stress. These findings are consistent with previous studies, which found that environmental stresses such as osmotic stress, salt and heat stress decreased seed germination due to the inhibition of starch catabolism under these conditions [29,36,37]. It has been found that the metabolite mobilization of starch and soluble sugars is critical for the maintenance of cell turgor and energy sources when seeds are subjected to salinity and osmotic stress [36].…”
Section: Discussionsupporting
confidence: 92%
“…Phenolamine, as a substrate of peroxidase, also participates in the scavenging of hydrogen peroxide and strengthening of the extraplastid cell wall, so it functions as an antioxidant and free radical scavenger, which can improve the ability of plants to resist abiotic stress [37]. The most important is that spermidine, a precursor in phenolamine synthesis, can enhance thermotolerance in rice seeds by modulating endogenous starch and polyamine metabolism [38]. Therefore, to characterize the possible role of the OsACT in thermotolerance of rice anther at anthesis, this gene was cloned and sequenced from SDWG005, 9311 and N22.…”
Section: Discussionmentioning
confidence: 99%
“…Application of spermidine also increased soluble sugars content, photosystem II (FPSII), photosynthetic electron transport rate (ETR), photochemical reaction of light energy ratio (Pr), variable fluorescence/maximum fluorescence ratio (Fv 0/Fm 0), stomatal conductance, and ultimately improved the photosynthesis and transpiration rate [68]. Fu et al [70] reported that exogenously applied spermidine increased rice tolerance to heat by modulating the antioxidants, polyamine metabolism, and starch accumulation.…”
Section: Induction Of Acclimation By Using Growth Regulators/protementioning
confidence: 99%